ON THE STUDY OF ANTHROPONYMIC INDICATORS USED IN THE WORK OF "HISTORY OF RASHIDI" - Jo‘oraboeva Gulruh Solijonovna; Saminov Abdumalik Inomjonovich (Western European Studies, 2024)
The article describes the anthroponymic indicators used in the work "History of Rashidi" and their types, such as indicators showing the social status of a person and emerging based on religious views.
Keywords: onomastics; anthroponymy; anthroponym; toponym